Development of Scientific Learning E-Book Using 3D Pageflip Professional Program - Raihan, Siti; Haryono, Haryono; Ahmadi, Farid (Innovative Journal of Curriculum and Educational Technology, 2018)
Curriculum 2013 prioritizes scientific-based learning. The scientific approach to familiarize students think high order thinking patterns. Based on preliminary analysis known that teachers have difficulties in designing a lesson plan scientifically based and requires a reading source procurement efforts. The development of technology can be used to develop educational products, such as e-books using the 3D Pageflip Professional program. Based on the literature study, this program has the advantage of digital interactive book design, flexible, efficient and effective as it integrates text, images, audio, and video. The study was conducted with the aim to provide problem-solving efforts related to adherence to the curriculum in 2013 through the development of scientific learning e-book. Researchers used the ADDIE model of research and development with the flow: analysis, design, development, implementation, and evaluation. The results of research in the form of an e-book product of scientific study that has been declared feasible by a team of experts (97.33% of material and media expert 98.7%), practitioners (supervisory 97.33%), and 90.6% with teachers' perceptions category very good. Practically, this research can be useful for teachers, governments, and researchers for services procurement expertise in the form of innovation in educational products.